2013
DOI: 10.7567/jjap.52.09ka04
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Evaluation of One-Axis Oriented Lead Zirconate Titanate Films Using Metal–Oxide Nanosheet Interface Layer

Abstract: Nanosheet Ca2Nb3O20 (ns-CN) layers with pseudo-perovskite-type crystal configuration were applied on the surface of polycrystalline metal substrates to achieve preferential crystal orientation of Pb(Zr,Ti)O3 (PZT) films for the purpose of enhanced ferroelectricity comparable to that of epitaxial thin films. PZT films with tetragonal symmetry (Zr/Ti=0.40:0.60) were fabricated by chemical solution deposition (CSD) on ns-CN-buffered Inconel 625 and SUS 316L substrates, while ns-CN was applied on the the substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 29 publications
1
22
2
Order By: Relevance
“…15,16,18,21 The nanosheets consisted of rectangular crystallites with thicknesses of approximately 2 nm and lateral sizes of approximately several hundred nanometers that expose the (001) plane of pseudo-perovskite-type lattice normal to the sheet surfaces [see high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) and electron diffraction (ED) images in Fig. 1].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…15,16,18,21 The nanosheets consisted of rectangular crystallites with thicknesses of approximately 2 nm and lateral sizes of approximately several hundred nanometers that expose the (001) plane of pseudo-perovskite-type lattice normal to the sheet surfaces [see high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) and electron diffraction (ED) images in Fig. 1].…”
Section: Methodsmentioning
confidence: 99%
“…The Pt layer was applied as a diffusion barrier as well as a bottom electrode. 21 Ferroelectric PZT films with thickness of approximately 300 nm and Zr/Ti ratio = 40/60, Pb(Zr 0.40 Ti 0.60 )O 3 , were fabricated on ns-CN-supported Pt/SUS (ns-CN/Pt/SUS) and Pt/SUS by a conventional chemical solution deposition (CSD) technique. Detail of the CSD coating was reported elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such ns-CN-coated glass substrates have been fabricated for achieving preferential crystal growth of (100)SrTiO 3 films 18) and (100)PZT/(100)LaNiO 3 heterstructures. 19) Furthermore, our group has reported that the ns-CN layer aligned the crystal orientation of PZT (simple perovskite) 20) and SrBi 4 Ti 4 O 15 (layered perovskite) films 21) on platinized silicon and stainless steel substrates. We expected the ns-CN layer would also align the crystal orientation of the BFO-and related materials because the unit size of BFO is significantly close to that of ns-CN.…”
Section: )3)mentioning
confidence: 95%